Progress, challenge and significance of building a carbon industry system in the context of carbon neutrality strategy - Caineng ZOU; Songtao WU; Zhi YANG; Songqi PAN; Guofeng WANG; Xiaohua JIANG; Modi GUAN; Cong YU; Zhichao YU; Yue SHEN (Petroleum Exploration and Development, 2023)
Carbon dioxide storage and utilization has become an inevitable trend and choice for sustainable development under the background of global climate change and carbon neutrality. Carbon industry which is dominated by CO2 capture, utilization and storage/ CO2 capture and storage (CCUS/CCS) is becoming a new strategic industry under the goal of carbon neutrality. The sustainable development of carbon industry needs to learn from the experiences of global oil and gas industry development. There are three types of “carbon” in the earth system. Black carbon is the CO2 that has not been sequestered or used and remains in the atmosphere for a long time; grey carbon is the CO2 that has been fixed or permanently sequestered in the geological body, and blue carbon is the CO2 that could be converted into products for human use through biological, physical, chemical and other ways. The carbon industry system covers carbon generation, carbon capture, carbon transportation, carbon utilization, carbon sequestration, carbon products, carbon finance, and other businesses. It is a revolutionary industrial field to completely eliminate “black carbon”. The development of carbon industry technical system takes carbon emission reduction, zero carbon, negative carbon and carbon economy as the connotation, and the construction of a low-cost and energy-efficient carbon industry system based on CCUS/CCS are strategic measures to achieve the goal of carbon neutrality and clean energy utilization globally. This will promote the “four 80%s” transformation of China's energy supply, namely, to 2060, the percentage of zero-carbon new energy in the energy consumption will be over 80% and the CO2 emission will be decreased by 80% to ensure the carbon emission reduction of total 80×108 t from the percentage of carbon-based fossil energy in the energy consumption of over 80%, and the percentage of CO2 emission from energy of over 80% in 2021. The carbon industry in China is facing three challenges, large CO2 emissions, high percentage of coal in energy consumption, and poor innovative system. Three strategic measures are proposed accordingly, including: (1) unswervingly develop carbon industrial system and ensure the achievement of carbon neutrality as scheduled by 2060; (2) vigorously develop new energy sources and promote a revolutionary transformation of China's energy production and consumption structure; (3) accelerate the establishment of scientific and technological innovation system of the whole CO2 industry. It is of great significance for continuously optimization of ecological environment and construction of green earth and ecological earth to develop the carbon industry system, utilize clean energy, and achieve the strategic goal of global carbon neutrality.